Answer:
The demonstration is showed below
Step-by-step explanation:
The distance betwenn two points is given by:
![d = \sqrt{(x2-x1)^2+(y2-y1)^2}](https://tex.z-dn.net/?f=d%20%3D%20%5Csqrt%7B%28x2-x1%29%5E2%2B%28y2-y1%29%5E2%7D)
If the point is equidistant from a point and a line, the distance must be equal. For the line let's select the point (x,-4), because the distance will be ortogonal, and is the small distance between a point and a line. So:
![\sqrt{(x-2)^2+(y-0)^2} = \sqrt{(x-x)^2+(y+4)^2}](https://tex.z-dn.net/?f=%5Csqrt%7B%28x-2%29%5E2%2B%28y-0%29%5E2%7D%20%20%3D%20%5Csqrt%7B%28x-x%29%5E2%2B%28y%2B4%29%5E2%7D)
Removing the squares:
(x-2)² + y² = (y+4)²
(x-2)² + y² = y² + 8y + 16
y² - y² - 8y = 16 - (x-2)²
8y = (x-2)² - 16
y = (1/8)*(x-2)² - 16/8
y = (1/8)*(x-2)² - 2